Omental Cyst: An Atypical Presentation in a Child Masquerading Tubercular Ascites with Severe Acute Malnutrition and Sickle Cell Disease - Samarth Gupta (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Introduction: Omental cysts are rare abdominal lesions which may be difficult to diagnose. The incidence of cystic lesions is about 1 per 140,000 general hospital admissions and about 1 per 20,000 pediatric hospital admissions. Most common presentation is abdominal distension. However, they may be an incidental finding or a painless abdominal mass and often mimicking ascites. The presentation is confusing in some cases which may result in mismanagement, added costs and trouble to the patient. Case Report: Here we encountered a case of a large omental cyst which was initially treated as tubercular peritonitis with ascites. The patient also suffered from malnutrition and was diagnosed a case of sickle cell disease adding to the dilemma in the final diagnosis. The USG report also suggested tubercular peritonitis with gross ascites. However, the CT scan suggested of omental cyst which was confirmed intra operatively and on histopathological examination. The cyst was successfully removed and the patient was discharged. Conclusion: Children presenting with abdominal distension should be carefully investigated to get to the correct diagnosis due to paucity of definitive signs and symptoms especially in omental cysts. Despite of all the investigations, the diagnosis may still be a dilemma. USG and CT is keystone in the diagnosis. Finally, once diagnosed an omental cyst can be safely removed.